1988
DOI: 10.1136/gut.29.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ulcerative reflux oesophagitis with colloidal bismuth subcitrate in combination with cimetidine.

Abstract: SUMMARY Twenty patients took part in a controlled double blind study comparing the efficacy of colloidal bismuth and cimetidine (800 mg at night) with cimetidine alone in the treatment of ulcerative reflux oesophagitis. Colloidal bismuth 120 mg was administered through an intraoesophageal tube four times a day. Cimetidine with colloidal bismuth gives significantly (p<0001) better results than cimetidine alone. Of 10 patients treated with cimetidine and bismuth, seven had no endoscopic signs of oesophagitis aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…The pathogenic role of H pylori in reflux oesophagitis was suspected in earlier studies37 38 while most other studies found no relationship 5-11. In contrast, the possible protective role of H pylori in reflux oesophagitis and other GORD related diseases such as Barrett's oesophagus and oesophageal adenocarcinoma has recently been suggested 12-14…”
Section: Discussionmentioning
confidence: 95%
“…The pathogenic role of H pylori in reflux oesophagitis was suspected in earlier studies37 38 while most other studies found no relationship 5-11. In contrast, the possible protective role of H pylori in reflux oesophagitis and other GORD related diseases such as Barrett's oesophagus and oesophageal adenocarcinoma has recently been suggested 12-14…”
Section: Discussionmentioning
confidence: 95%
“…In the latter group, healing of oesophagitis was significantly better. 57 At entry evidence of H pylori was present in nine patients-in the five patients treated with combination therapy cultures were negative within one week, while they were negative in two of four patients treated with cimetidine alone. Although these findings do suggest a benefit for eradication therapy at least in patients with severe oesophagitis, patient numbers were small, and the eYcacy of diagnostic tests for H pylori is limited during continued acid suppression.…”
Section: Eradication Therapy In Patients With Gordmentioning
confidence: 92%
“…[56][57][58][59][60][61][62][63][64][65][66][67] Although all of the studies did not have adequate numbers of patients or control populations, the overall prevalence of H pylori is not significantly greater in patients with GORD than what would be expected in the general population (table 1). H pylori had been diagnosed by various methods in just 35% of almost 700 patients with varying degrees of reflux disease (table 1).…”
Section: H Pylori and Gord: The Epidemiological Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble salts such as bismuth subsalicylate, sodium triglycollamate and trioglycolate have been used parenterally to treat infectious diseases (notably syphilis). Bismuth salicylate, subcarbonate, subcitrate, subnitrate, glycobiasol and other salts are used orally, or have been reported for use in the treatment of reflux esophagitis (Borkent and Beker 1988), gastritis (McNulty et al 1986), indigestion (Hailey and Newsom 1984), diarrhea, and other gastrointestinal disorders. In particular, colloidal bismuth subcitrate (CBS), when given in combination with antibiotics, is very effective at concentrations of 10 -16 mg Bi L À1 against mucosal Campylobacter pylori.…”
Section: 3mentioning
confidence: 99%